(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Reconstruction of the skull using cranial implants is essential to protect intracranial structures and restore cerebral hemodynamics when accidents, disease, or cancer cause craniofacial anomalies. The two main goals of a cranioplasty treatment are protecting the brain inside the skull and achieving a desired cosmetic result. With the development of digital 3D technology, Patient-Specific Implants (PSI) have been widely used for surgical correction of congenital, post-traumatic, or post-surgical abnormalities. PSIs must mimic the natural structure of bones, be biocompatible, lightweight, and stress-resistant. Interface joints and fastening mechanisms are essential for a robust connection to the injured cranium. With an emphasis on four typical cranial flaws-small frontal defects, big lateral defects, large bilateral defects, and zygomatic bone defects-this study examines the use of several methodologies for PSI construction. In this field, digital subtraction after mirror imaging on the normal side of the skull is the most widely used technique for implant fabrication. Shape-based interpolation is another technique for creating implants that are unique to the defect. To compare the two methods, we used the Edge Gap Factor (EGF), defined as the ratio of the interpolated implant’s mode edge deviation to that of the mirrored implant. An EGF < 1 indicates superior performance of the interpolation method, while an EGF > 1 indicates superior performance of the mirroring method. Both methods perform similarly when EGF = 1. The major objective of this study is to verify if the gap is homogenous and whether the spacing between neighboring surface clusters is constant during the gap length through the analysis of EGF. For each of the four cases, the two implants that were regenerated utilizing the two procedures had their gap sizes compared to identify which one was the best match. The degree to which the implant fills the defect was assessed by measuring the gaps between the implant and the skull interface. Guidelines for the best implant generation process are provided by this study, which considers four distinct cranial deformities that account for the majority of cases of skull defect repairs.